Detección de anticuerpos anti-Mycobacterium bovis en sangre y calostro bovino - Ruiz Menna, Victoria Aymara; Garro, Carlos Javier; Felippa, E.; Abdala, Alejandro Ariel; Suarez Archilla, Guillermo; Sammarruco, Romina Ayelén; Delgado, Fernando Oscar; Garbaccio, Sergio Gabriel (Universidad Nacional del Centro de la Provincia de Buenos Aires, 2023)
Poster